Search for dark matter produced in association with a Higgs boson decaying to γγ or τ + τ − at √s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2018)
A search for dark matter particles is performed by looking for events with large transverse momentum imbalance and a recoiling Higgs boson decaying to either a pair of photons or a pair of τ leptons. The search is based on proton-proton collision data at a center-of-mass energy of 13 TeV collected at the CERN LHC in 2016 and corresponding to an integrated luminosity of 35.9 fb−1 . No significant excess over the expected standard model background is observed. Upper limits at 95% confidence level are presented for the product of the production cross section and branching fraction in the context of two benchmark simplified models. For the Z0 -two-Higgs-doublet model (where Z0 is a new massive boson mediator) with an intermediate heavy pseudoscalar particle of mass mA = 300 GeV and mDM = 100 GeV, the Z0 masses from 550 GeV to 1265 GeV are excluded. For a baryonic Z0 model, with mDM = 1 GeV, Z0 masses up to 615 GeV are excluded. Results are also presented for the spin-independent cross section for the dark matter-nucleon interaction as a function of the mass of the dark matter particle. This is the first search for dark matter particles produced in association with a Higgs boson decaying to two τ leptons.